2007
DOI: 10.1007/s11517-007-0296-5
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory measurement of shoulder and elbow kinematics through inertial and magnetic sensors

Abstract: Inertial and magnetic measurement systems (IMMSs) are a new generation of motion analysis systems which may diffuse the measurement of upper-limb kinematics to ambulatory settings. Based on the MT9B IMMS (Xsens Technologies, NL), we therefore developed a protocol that measures the scapulothoracic, humerothoracic and elbow 3D kinematics. To preliminarily evaluate the protocol, a 23-year-old subject performed six tasks involving shoulder and elbow single-joint-angle movements. Criteria for protocol validity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
266
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 264 publications
(278 citation statements)
references
References 32 publications
11
266
0
1
Order By: Relevance
“…1 We assume a heading error and thus replace by . Taking the scalar product with on both sides and making use of the fact that yields…”
Section: Joint Constraint In Angular Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 We assume a heading error and thus replace by . Taking the scalar product with on both sides and making use of the fact that yields…”
Section: Joint Constraint In Angular Ratesmentioning
confidence: 99%
“…However, the orientation of each IMU with respect to its body segment must be known to derive useful kinematic quantities. This is commonly achieved by accurate manual placement of the IMUs [1] or by asking the subject to perform tedious calibration movements [3]. However, it was recently demonstrated that sensor-to-segment orientations can also be determined from the data of arbitrary upper or lower limb motions [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the validity of the IMC system for measurement of kinematics (Cutti et al, 2008;Faber et al, 2013b;Godwin et al, 2009;Luinge and Veltink, 2005;Plamondon et al, 2007;Roetenberg et al, 2005). However, the number of studies testing the validity of the system for the assessment of the kinetics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is an almost unexplored topic in motion analysis in general [2,9,14,15], and for the upper extremity specifically. The paper by Parel et al [21] gives a contribution on this regard, by assessing the agreement between two scapula-tracking systems (scapula tracker [18] and spine tracker [10]), based on two different motion analysis technologies, namely opto-eletronic and inertial and magnetic sensors [10,11]. Filling a gap in current literature, the paper points out a clear set of conditions for agreement between systems for scapula tracking, based on state-ofthe-art parameters, i.e., within-protocol repeatability and Bland-Altman Limits of Agreement.…”
Section: Fil Rouge: the Papers In Perspectivementioning
confidence: 99%